Presuppositions and ethical implications of the dialectical metaphysics in Plato’s Seventh Letter - Rohden, Luiz (Revista Archai, 2016)
Assuming that Gadamer’s philosophical hermeneutics has incorporated several aspects of Plato’s philosophy, we aim to challenge some ethical presuppositions of dialectical metaphysics. For this reason, we have chosen Plato’s Seventh Letter because it reveals a clear interconnection between dialectical metaphysics and ethics. We will try to show how the Platonic dialectical metaphysics consists in the upward and downward movement of the principles; the first theoretical and practical exercise paves metaphysics, and the second practical and theoretical exercise establishes ethics. In Gadamer’s discourse, this is shown in the dialogical way of proceeding of philosophical hermeneutics which consists in the permanent intersection between the path of the word itself to the concept and vice versa. These indications are traces of a conception of metaphysics distinct from the one that has been explored by the contemporary philosophical tradition in general. Firstly, in order to establish the theoretical grounds of my argument, I will mention some of the ethical presuppositions of dialectical metaphysics and, secondly, we will demonstrate that the methodology peculiar to dialectical metaphysics is an ethical exercise.